Oral complications associated to organ and tissue transplants: a literature review - Santos, Paulo Sergio da Silva; Bitu, Fabrício; Coracin, Fabio Luiz; Mancusi Sobrinho, Romano; Lima, Roberto Brasil (Brazilian Journal of Transplantation, 2009)
Oral complications may be important for investigate systemic complications especially related to the immunosuppression condition in transplants and with risk of infections. With the increasing amount of organ and tissue transplanted patients, it has become essential to have multidisciplinary teams to take care of transplanted patients, and among them, dentistry can and should be a part. This literature review intends to present and discuss the relevance of oral complications related to organ and tissue transplants before and after the transplant that can lead to severe complications interfering in a successful medical therapy.